Oral immunotherapy in children for the most common food allergy - Kruczkowska, Adrianna; Kanturski, Andrzej; Tomczyk, Bartosz; Wilk, Mateusz; Ptak, Jakub; Gomułka, Krzysztof (Medical Studies/Studia Medyczne, 2022)
Nowadays, the incidence of food allergies is increasing. While strict allergen avoidance remains the most important therapeutic approach, oral immunotherapy is increasingly being used to desensitize and induce tolerance in children. Oral immunotherapy is a possible treatment for food allergies, which includes the administration of gradually increasing doses of the allergen. While most children can be desensitized, or even gain sustained unresponsiveness, oral immunotherapy involves a high risk of side effects or allergic responses with a need to use epinephrine, and the long-term effectiveness is unknown. In this paper, we summarize recent clinical trials in which oral immunotherapy has been used to treat common food allergies: to cow’s milk, peanuts, and chicken eggs.